2017
DOI: 10.1111/aji.12673
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs downregulated following immune activation of rat testis

Abstract: Review of the literature has revealed that these miRNAs also play important roles in the maintenance of fertility, formation and elimination of cancer, and development of the male reproductive tract. Further study will lead to a greater understanding of male reproductive immunology and related health issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
3
20
0
Order By: Relevance
“…In addition, TLR stimulation elevates the synthesis of proinflammatory cytokines such as IL-1β and TNF (both of which showed elevated mRNA expression in our study) so perhaps TLR-dependent pathways and not NF-κB is the predominant activation pathway for HIF-1 in the testis. Recently we have also demonstrated that expression of a number of microRNAs in the testis are downregulated by LPS including miRNAs involved in regulating the NF-κB pathway [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TLR stimulation elevates the synthesis of proinflammatory cytokines such as IL-1β and TNF (both of which showed elevated mRNA expression in our study) so perhaps TLR-dependent pathways and not NF-κB is the predominant activation pathway for HIF-1 in the testis. Recently we have also demonstrated that expression of a number of microRNAs in the testis are downregulated by LPS including miRNAs involved in regulating the NF-κB pathway [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…let-7f-5p may prove to be a valid molecular biomarker for carcinoma. It is correlated with suppression of the target gene HMGA2 [85], and plays important roles in the maintenance of fertility [86], cell proliferation [87], and neuronal differentiation [88]. let-7f-5p also inhibits the porcine reproductive and respiratory syndrome virus by targeting MYH9 [89].…”
Section: Potential Functions Of Highly Expressed Mirnas In Biofluid Ementioning
confidence: 99%
“…Furthermore, miRNAs serve as crucial contributors of orchitis. For instance, it was previously revealed that multiple inflammation-associated miRNAs were inhibited in response to LPS exposure in murine testis models (Parker and Palladino 2017). Moreover, let-7, miR-17, and miR-449a exerted overlapping regulatory effects on male fertility.…”
Section: Introductionmentioning
confidence: 99%